Precision Machining of Nimonic C 263 Super AlloyUsing WEDM - Mouralová, Kateřina; Beneš, Libor; Bednář, Josef; Zahradníček, Radim; Prokeš, Tomáš; Fiala, Zdeněk; Fries, Jiří (MDPI, 2020)
Wire electrical discharge machining (WEDM) is an unconventional and very efficient technology for precision machining of the Nimonic C 263 super alloy, which is very widespread, especially in the energy, aerospace and automotive industries. Due to electrical discharge, defects in the form of cracks or burned cavities often occur on the machined surfaces, which negatively affect the correct functionality and service life of the manufactured components. To increase the efficiency of the machining of Nimonic C 263 using WEDM, in this study, extensive design of experiments was carried out, monitoring input factors in the form of machine parameters like Pulse off time, Gap voltage, Discharge current, Pulse on time and Wire feed, the output of which was comprehensive information about the behaviour of such machined surfaces, which allowed the optimization of the entire machining process. Thus, the optimization of the Cutting speed was performed in relation to the quality of the machined surface and the machining accuracy, as well as an analysis of the chemical composition of the machined surfaces and a detailed analysis of the lamella using a transmission electron microscope. A detailed study of the occurrence of surface or subsurface defects was also included. It was found that with the help of complex optimization tools, it is possible to significantly increase the efficiency of the machining of the Nimonic C 263 super alloy and achieve both financial savings in the form of shortened machine time and increasing the quality of machined surfaces.

Wire electrical discharge machining (WEDM) is an unconventional and very efficient technology for precision machining of the Nimonic C 263 super alloy, which is very widespread, especially in the energy, aerospace and automotive industries. Due to electrical discharge, defects in the form of cracks or burned cavities often occur on the machined surfaces, which negatively affect the correct functionality and service life of the manufactured components. To increase the efficiency of the machining of Nimonic C 263 using WEDM, in this study, extensive design of experiments was carried out, monitoring input factors in the form of machine parameters like Pulse off time, Gap voltage, Discharge current, Pulse on time and Wire feed, the output of which was comprehensive information about the behaviour of such machined surfaces, which allowed the optimization of the entire machining process. Thus, the optimization of the Cutting speed was performed in relation to the quality of the machined surface and the machining accuracy, as well as an analysis of the chemical composition of the machined surfaces and a detailed analysis of the lamella using a transmission electron microscope. A detailed study of the occurrence of surface or subsurface defects was also included. It was found that with the help of complex optimization tools, it is possible to significantly increase the efficiency of the machining of the Nimonic C 263 super alloy and achieve both financial savings in the form of shortened machine time and increasing the quality of machined surfaces.
Precision Machining of Nimonic C 263 Super AlloyUsing WEDM
Keywords: WEDM; wire electrical discharge machining; nimonic; design of experiment; machining parameters; WEDM; wire electrical discharge machining; nimonic; design of experiment; machining parameters